O impacto da covid-19 no sistema carcerário paraense e a aplicação da lei 13.257/2016 no estado de pandemia (covid-19) - análise jurisprudencial no TJPA - LIRA, Rafael Pedro Costa (2022)
This work has as its general objective to present the problems faced in the period of COVID-19 pandemic in the prison system of Pará and in the application of releasing measures upon the conversion of house arrest of mothers with children under 12 years old, a corollary to the application of law 13.257/2016, which altered the criminal procedural logic. Thus, studies were carried out on the implication of the pandemic in the logic of incarceration, based on government data, scientific articles, books and institutions that are guided by social justice, as well as a practical study, through jurisprudential analysis at the Court of Justice of the State of Pará - TJPA, in relation to Habeas Corpus with the scope of application of the releasing measure that seeks house arrest as a guarantor of the best protective childhood for the child and the health of his/her family in the period of the COVID-19 pandemic, therefore observing how the judiciary in its decisions, as well as the Public Ministry in its opinions, in relation to constitutional remedies, are concerned with guaranteeing a constitutional reading of the case and the particularity of the COVID-19 pandemic.